2016
DOI: 10.1136/vetreccr-2016-000291
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic investigation of Marek's disease in a turkey

Abstract: A six-month-old female turkey from a commercial growing unit was evaluated at postmortem examination for investigation of suspected viral lymphoproliferative disease. Clinically, the turkey was dull and subdued, and relatively unresponsive to external stimuli. The main gross postmortem findings were diffusely enlarged spleen, kidneys and liver, with multifocal cream foci. The lungs were atelectatic, and mild segmental mural thickening of the small intestines was observed. Impression smears taken during postmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In experimental studies, the lesions seen in the nerves were either rarely encountered or not at all. However, it has been noted that lymphoproliferative lesions occurring in visceral organs in chickens are also seen in turkeys (Hughes et al, 2016;Nair et al, 2020). In the acute form, while pleomorphic lymphocyte deposits were observed in the visceral organs, it was reported that clinical findings were less pronounced, in this case, deaths could increase rapidly and reach 70% in large outbreaks (Nair et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In experimental studies, the lesions seen in the nerves were either rarely encountered or not at all. However, it has been noted that lymphoproliferative lesions occurring in visceral organs in chickens are also seen in turkeys (Hughes et al, 2016;Nair et al, 2020). In the acute form, while pleomorphic lymphocyte deposits were observed in the visceral organs, it was reported that clinical findings were less pronounced, in this case, deaths could increase rapidly and reach 70% in large outbreaks (Nair et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Although histopathological changes in Marek's disease are well defined in chickens, limited findings have been reported in turkeys (Pennycott and Venugopal, 2002). It has been reported that the most characteristic histopathological finding is pleomorphic lymphocytes and mononuclear cells infiltration in multiple organs as in chicken (Hughes et al, 2016;Nair et al, 2020;Pattison et al, 2008). Nevertheless, it has been stated that macroscopic and microscopic findings observed in chickens are not frequently observed or not evident in turkeys (Blake-Dyke and Baigent S, 2013; Deuchande et al, 2012;Hughes et al, 2016;Pennycott and Venugopal, 2002;Voelckel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations